Enhancing Psychiatry Education with WHO mhGAP Videos: Insights from Undergraduate Medical Students - Alfahal, Mohammed; Elmuttalut, Mohammed (International Journal of Innovative Research in Medical Science, 2024)
Background: Psychiatry training is an essential component of undergraduate medical education, preparing future physicians to effectively address mental health disorders. The WHO’s Mental Health Gap Action Programme (mhGAP) was developed to mitigate mental health care gaps, particularly in low- and middle-income countries. Not much information is available on the relevance and effectiveness of using these videos in enhancing the training process in undergraduate medical education. Aims: This study aimed to evaluate the effectiveness of WHO mhGAP training videos in enhancing psychiatry education for undergraduate medical students, specifically examining improvements in understanding psychiatric concepts, clinical skills, learning engagement, and cultural relevance. Methods: A cross-sectional study was conducted with 80 medical students in the psychiatry rotation at Al-Rayan National College of Medicine. Data was collected using a structured questionnaire addressing mhGAP video effectiveness, learning experience, and cultural relevance. Descriptive statistics were utilized to analyze the findings. Results: The study revealed that 92.5% of students reported that the mhGAP videos significantly enhanced their understanding of psychiatric concepts. Additionally, 73.75% of participants found the videos particularly effective in providing practical examples and case studies, while 72.5% felt that the videos enhanced their clinical readiness. In terms of engagement, 58% of students agreed that the videos were engaging and effectively captured their attention. The videos were also praised for their cultural relevance, with 60% of students finding the use of Arabic language more beneficial, and 55% feeling comfortable with the Lebanese accent used in the videos. Conclusion: WHO mhGAP videos were perceived as highly relevant and effective tools for enhancing the understanding of complex psychiatric concepts, clinical skills, preparedness, and engagement, while addressing cultural needs. Integrating these linguistically and culturally relevant videos into medical curricula is highly recommended to contextualize and improve psychiatry education in different educational settings.